Incumbent and Entrant Rivalry in a Deregulated Industry - Madsen, Tammy L.; Walker, Gordon (Organization Science, 2007)
This paper examines how two general cohorts of firms, entrants and incumbents, differ in their competitive intensity following price and entry deregulation in the trucking industry from 1980 to 1993. The results demonstrate that the competitive strength associated with entrants’ experience is reduced as they grow. However, organizational size dampens the positive effect of competitive experience on the exit rate more slowly for incumbents that were large at deregulation than it does for entrants. The results suggest that two types of firms exert the strongest pressure on rivals: entrants that gain experience but remain small under deregulation, and incumbents that are large but had limited prederegulation experience.